Disproportion between the Peruvian Amazonian megadiverse mammalian fauna and the available molecular information - Martínez Altamirano, José Luís (2024)
Peru holds a high mammalian diversity in its Amazonian region, with 326 species. However, our knowledge about the actual diversity is still considered incomplete, and the molecular information for those species in genetic databases is even less comprehensive. To assess the availability of genetic information for Peruvian Amazonian mammals relative to known diversity, we surveyed the Amazonian mammals with at least one molecular marker in the most widely used repositories for nucleotide sequences, GenBank and BOLD Systems. Our survey focused on widely used molecular markers in evolutionary biology-cytochrome b [cyt-b], cytochrome oxidase I [COI], 12S ribosomal RNA [12S], and the mitogenome [mit]-derived from Peruvian Amazon mammals. Additionally, to gain insights into the current mammalian sampling effort in Peruvian Amazonia, we generated a map of unique sampling localities and a heat map, utilizing 41951 records, which identified six major information gaps. This comprehensive analysis found 1597 genetic sequences corresponding to 180 mammalian species (55.2% of Peruvian Amazonian species): COI (38 species), cyt-b (167 species), 12S (56 species), and mitogenome (16 species). Taxonomically, Rodentia (53 species, four markers), Chiroptera (63 species, three markers), and Didelphimorphia (27 species, four markers) represented most molecular data, with a concentration of molecular markers in the orders Chiroptera (703) and Rodentia (499). Geographically, the Loreto department has the largest genetic information (530 records, 99 species). These results confirm a worrying underrepresentation of Peruvian Amazonian diversity in molecular databases. Consequently, we advocate for the use of scientific collections as an alternative source to systematically generate genetic information for the Amazonian mammal diversity in Peru to compensate for the current underrepresentation.